2011
DOI: 10.1167/iovs.11-8076
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Healthy Chinese Subjects

Abstract: Age is critical for evaluation of choroidal thickness. However, SFCT has no correlation with age in subjects younger than 60 years of age. In subjects older than 60 years of age, SFCT was significantly negatively correlated with age, and decreased by 5.40 μm for each year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
178
6
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(223 citation statements)
references
References 15 publications
37
178
6
2
Order By: Relevance
“…This finding may be because the photoreceptor is most active at the macular center concave, where it has no direct retinal blood supply; thus, the choroid is thickest underneath the fovea because it must provide adequate blood supply. [16][17][18] In the Chinese population, the subfoveal choroidal thickness is not correlated with age in subjects younger than 60 years, whereas the subfoveal choroidal thickness is relatively thinner and significantly negatively correlated with age in the population older than 60 years. 18 Meanwhile, the choroidal thickness was shown to increase along with the severity of the diopter, 19 and a pattern of diurnal variation exists.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding may be because the photoreceptor is most active at the macular center concave, where it has no direct retinal blood supply; thus, the choroid is thickest underneath the fovea because it must provide adequate blood supply. [16][17][18] In the Chinese population, the subfoveal choroidal thickness is not correlated with age in subjects younger than 60 years, whereas the subfoveal choroidal thickness is relatively thinner and significantly negatively correlated with age in the population older than 60 years. 18 Meanwhile, the choroidal thickness was shown to increase along with the severity of the diopter, 19 and a pattern of diurnal variation exists.…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18] In the Chinese population, the subfoveal choroidal thickness is not correlated with age in subjects younger than 60 years, whereas the subfoveal choroidal thickness is relatively thinner and significantly negatively correlated with age in the population older than 60 years. 18 Meanwhile, the choroidal thickness was shown to increase along with the severity of the diopter, 19 and a pattern of diurnal variation exists. 20 Therefore, we carried out all of the choroidal and retinal Retinal and choroidal thickness evaluation by SD-OCT C Xin et al…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have measured choroidal thickness in both normal subjects and those with ocular disease using EDI-OCT and SS-OCT 2,7,9,13,[20][21][22][23][24] . Retinal studies are typically performed with specific software provided by the different OCT manufacturers; however, manual segmentation is required in all cases in which choroidal thickness or volume are measured.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to study repeatability and reproducibility because of the manual segmentation and the other mentioned parameters. Comparison with previous studies is difficult because of the different line scans performed with various instruments, variability in the ages and sexes of the populations being evaluated or the different statistical methodologies used.A number of studies have characterized healthy choroidal thickness, one of the most studied parameters, as having mean subfoveal choroidal thickness values lower than 300µm 7,9,10,20,23,25 or higher that 300µm 6,8,13,24,[26][27][28] , with a range from 202.6±83.5µm 9 to 355±73µm 8 or 354±111µm …”
mentioning
confidence: 99%
“…Histological studies have shown that choroidal thickness may decrease by 80μm by the age of 90 (19). Ding et al's study has reported that choroidal thickness gets thinner and decreases in patients older than 60 while this condition is not applicable to people younger than 60 (20). Because our study was not conducted among subjects of different age groups but among young adults only, we were unable to identify how choroidal thickness change with age.…”
Section: Methodsmentioning
confidence: 84%